Beauty pays : why attractive people are more successful - Hamermesh, Daniel S. (Princeton, NJ ; Oxford : Princeton University Press, 2011)
Most of us know there is a payoff to looking good, and in the quest for beauty we spend countless hours and billions of dollars on personal grooming, cosmetics, and plastic surgery. But how much better off are the better looking? Based on the evidence, quite a lot. The first book to seriously measure the advantages of beauty, this work demonstrates how society favors the beautiful and how better-looking people experience startling but undeniable benefits in all aspects of life. The author, an economist, shows that the attractive are more likely to be employed, work more productively and profitably, receive more substantial pay, obtain loan approvals, negotiate loans with better terms, and have more handsome and highly educated spouses. He explains why this happens and what it means for the beautiful and the not-so-beautiful among us. Exploring whether a universal beauty standard exists, he illustrates how attractive workers make more money, how these amounts differ by gender, and how looks are valued differently based on profession. The author wonders whether extra pay for good-looking people represents discrimination, and, if so, who is discriminating. He investigates the commodification of beauty in dating and how this influences the search for intelligent or high-earning mates, and even considers whether government programs should aid the ugly. Also discussed is whether the economic benefits of beauty will persist into the foreseeable future and what the "looks-challenged" can do to overcome their disadvantage. Reflecting on a sensitive issue that touches everyone, this book proves that beauty's rewards are anything but superficial.
The economics of beauty -- In the eye of the beholder -- Beauty and the worker -- Beauty in specific occupations -- Beauty and the employer -- Lookism or productive beauty, and why? -- Beauty in markets for friends, family, and funds -- Legal protection for the ugly -- Prospects for the looks-challenged.
Includes bibliographical references and index.
Keywords: Success in business; Success; Beauty, Personal; Beauty, Personal; Success; Success in business; Nonfiction